2020
DOI: 10.5194/se-11-2257-2020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basement rocks on fluid evolution during multiphase deformation: the example of the Estamariu thrust in the Pyrenean Axial Zone

Abstract: Abstract. Calcite veins precipitated in the Estamariu thrust during two tectonic events are studied in order to (i) decipher the temporal and spatial relationships between deformation and fluid migration in a long-lived thrust and (ii) determine the influence of basement rocks on the fluid chemistry during deformation. Structural and petrological observations constrain the relative timing of fluid migration and vein formation, whilst geochemical analyses (δ13C, δ18O, 87Sr∕86Sr, clumped isotope thermometry, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…(2) Waters derived from deeper Triassic aquifers or basement fluids (Muñoz-López et al, 2020) injected into the shallower Jurassic carbonate aquifers, as evidenced in the central Paris Basin Matray, 1993a, 1993b;Worden and Matray, 1995);…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…(2) Waters derived from deeper Triassic aquifers or basement fluids (Muñoz-López et al, 2020) injected into the shallower Jurassic carbonate aquifers, as evidenced in the central Paris Basin Matray, 1993a, 1993b;Worden and Matray, 1995);…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This would suggest fluidrock interaction between the cement-forming fluids and the radiogenic silicic clasts of the host rocks sourced from the Palaeozoic basement in the Axial Zone. Muñoz-L opez et al (2020a) studied the influence of basement rocks on fluid chemistry in other outcrops elsewhere in the Pyrenees, and concluded that calcite cements precipitated from fluids that strongly interacted with basement rocks could have resulted in a significantly higher 87 Sr/ 86 Sr ratio (>0.710) in nearby areas. The 87 Sr/ 86 Sr ratios of Cc3 in our study area are lower than this value, probably because carbonate clasts dominate over silicic clasts in the zone where Cc3 precipitated.…”
Section: Fluid Origin Of Calcite Cementsmentioning
confidence: 99%
“…Many studies mainly focus on unravelling the relationships between fluid flow, deformation and fluid–rock interaction in fold‐and‐thrust belts, whereas their adjacent foreland basins are significantly less well‐documented. For example, in the South Pyrenees, an ideal natural laboratory due to its well‐preserved and well‐exposed outcrops, most studies focused on the cover thrust sheets (Travé et al ., 1997; Lacroix et al ., 2011, 2014, 2018; Beaudoin et al ., 2015; Crognier et al ., 2018; Cruset et al ., 2018, 2020a,b; Nardini et al ., 2019; Muñoz‐López et al ., 2020a,b), whereas only a few studies involved the Ebro Foreland Basin (Travé et al ., 2000, 2007; Cruset et al ., 2016). On the other hand, compressional settings have high potential for carbon capture and storage (CCS) (Sun et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%